Quality of TB care among people living with HIV: Gaps and solutions. (December 2019) - Naidoo, Kogieleum; Gengiah, Santhanalakshmi; Singh, Satvinder; Stillo, Jonathan; Padayatchi, Nesri
Abstract: Tuberculosis (TB) is the leading infectious cause of death among people living with HIV, causing one third of AIDS-related deaths globally. The concerning number of missing TB cases, ongoing high TB mortality, slow reduction in TB incidence, and limited uptake of TB preventive treatment among people living with HIV, all indicate the urgent need to improve quality of TB services within HIV programs. In this mini-review we discuss major gaps in quality of TB care that impede achieving prevention and treatment targets within the TB-HIV care cascades, show approaches of assessing gaps in TB service provision, and describe outcomes from innovative quality improvement projects among HIV and TB programs. We also offer recommendations for measuring quality of TB care.